Clustering Routing Protocol for Mobile Wireless Sensor Networks Based on Dynamic Network Partition - Cao, Luzhou (International Journal of Online and Biomedical Engineering (iJOE), 2018)
To prolong the network life and improve the network performance, a new clustering routing protocol which uses dynamic network to divide and consider the residual energy of sensor nodes is proposed. The design and simulation of the clustering scheme for mobile wireless sensor networks are also studied. The results show that the protocol controls the number of cluster heads by region division of the network and balances its distribution in wireless sensor networks according to the latest location of the sink node. At the same time, the residual energy of nodes is considered to balance the energy consumption of the network when the cluster head is elected. The protocol effectively solves the problem of uneven distribution of cluster heads in time and space and energy consumption of each node in the LEACH protocol. Compared with the LEACH protocol, M-LEACH effectively prolongs the network life. From this, it is seen that the application of M-LEACH protocol in mobile wireless sensor network clustering routing is effective.